The presence of (hi)stories: on the literary reflexion of Europe in novels by Robert Menasse and Georgi Gospodinov - Bischoff, Doerte (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2026)
Since the end of the Cold War, the narratives of remembrance which often distinguished Europe’s West and East from each other have lost their power to persuade. In contemporary German literature, several reconstructions of family histories instead describe border crossings and entanglements between East and West. Many of these texts also ask how far it is possible to narrate European stories of this kind, given the heterogeneity, ruptures, and voids which are often at their core. Against the background of works which shape Europe as ‘Memoryland’, this article reads Robert Menasse’s The Capital and Georgi Gospodinov’s Time Shelter in order to identify the processes of individual and collective remembering on which they reflect. In so doing, the article reveals remarkable similarities between the two novels’ concern with the renationalization of memory, their recognition that dementia destroys memory but also preserves it, and their ambivalence towards the symbolic representation or performance of the past.
Keywords: culture of remembrance; narrative; Europe; history of violence; post-Wende literature; nation; nationalism